The spread of nuclear weapons a debate - Sagan, Scott Douglas 1955-; Waltz, Kenneth Neal 1924-2013 (Norton, 1995)
If the nuclear balance of terror helped maintain the "long peace" between the United States and the Soviet Union, will the continuing spread of nuclear weapons also help stabilize international relations in this post-cold war age? In The Spread of Nuclear Weapons: A Debate, two major scholars of international politics debate this critical issue. Kenneth Waltz, the dean of neorealist theory in international relations, argues that fears about nuclear proliferation are exaggerated: "More may be better," since new nuclear states will wisely use their weapons to deter other states from attacking. Scott Sagan, the leading proponent of organizational theories of international politics, argues that nuclear proliferation will make the world less stable: "More will be worse," as new nuclear states will lack the organizational structures to ensure safe and rational control of their weapons. The global community has long been fascinated with, and frightened by, nuclear weapons. This short and engaging book will be required reading for citizens and statesmen, as well as scholars and students, as we try to understand the role that nuclear weapons will play in the future world order.
Keywords: Proliferatie (kernwapens); Arms race; Nuclear nonproliferation; Nuclear weapons; Rüstungswettlauf; Nonproliferation; Kernwaffe; Aufsatzsammlung